2021
DOI: 10.1128/mbio.03381-20
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative and Conserved Cell Wall Enzyme That Can Substitute for the Lipid II Synthase MurG

Abstract: The cell wall is a stress-bearing structure and a unifying trait in bacteria. Without exception, synthesis of the cell wall involves formation of the precursor molecule lipid II by the activity of the essential biosynthetic enzyme MurG, which is encoded in the division and cell wall synthesis (dcw) gene cluster. Here, we present the discovery of a cell wall enzyme that can substitute for MurG. A mutant of Kitasatospora viridifaciens lacking a significant part of the dcw cluster, including murG, surprisingly pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 77 publications
1
13
0
Order By: Relevance
“…We previously showed that K. viridifaciens alpha , an unstable L-form strain obtained after induction with penicillin and lysozyme, can either grow filamentous or wall-deficient depending on the osmolarity of the media (Ramijan et al, 2018; Zhang et al, 2021). Using gradient plates, we indeed found that alpha could readily switch between these distinct morphologies (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously showed that K. viridifaciens alpha , an unstable L-form strain obtained after induction with penicillin and lysozyme, can either grow filamentous or wall-deficient depending on the osmolarity of the media (Ramijan et al, 2018; Zhang et al, 2021). Using gradient plates, we indeed found that alpha could readily switch between these distinct morphologies (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…K. viridifaciens Δ dcw was found to be unable to revert to the walled state, caused by the absence of a large part of the dcw cluster (Zhang et al, 2021). Interestingly, our gradient plates reveal colonies at an LPMA percentage of 20% LPMA, indicating that these L-forms could tolerate a much lower concentration of osmolytes than previously thought.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this, a 20 nt spacer sequence was introduced into the sgRNA scaffold by PCR using forward primers KSβ_TF or KSβ_NT2F together with reverse primer SgTermi_R_B. The PCR products were cloned into pGWS1370 55 via NcoI / BamHI restriction sites. The resulting constructs pGWS1516 (targeting template strand of KSβ, control) and pGWS1517 (targeting non-template strand of KSβ) were then introduced into Streptomyces sp.…”
Section: Crispri Technologymentioning
confidence: 99%